STUDI ANALISIS WACANA MODEL VAN DIJK PADA PEMBERITAAN VOA INDONESIA TENTANG KASUS PELECEHAN SEKSUAL DI TEMPAT IBADAH "X" DI DEPOK - Eduardus Sultan Putra Aditama, (2023)
Every report that is made by the media has a discourse contained in it, moreover the topic raised is a case that is quite interesting to the public. The discourse contained in a report usually has a purpose that the author wants to convey to the reader. One of the example's news about the case of sexual violence at the "X" worship house in Depok. This study aims to find out the discourse on reporting on cases of sexual violence at the "X" worship house in Depok. The method used is descriptive qualitative using data sources of 3 news documents published in the period June 2020 to January 2021. The data analysis technique used in this study is the Van Dijk model of discourse analysis, with three dimensions of analysis, text, social cognition, and social context. The approach used in this study is a qualitative approach to see how the discourse is formed in the news in this study. The results of this study indicate that there is no media bias in the three reports made by VOA Indonesia. Basically, VOA Indonesia tries to stay away from partiality and stay neutral by reporting according to the facts on the ground. The discourse that is formed in the news is indirectly VOA Indonesia shows that there are still cases of sexual violence in Indonesia that are still handled seriously and maximally by law enforcement officials and parties involved in this case. Another discourse formed from this news is that men can also be victims of sexual harassment and the impact experienced is no less bad than that of female victims.